The trend of software cost estimation in Ethiopia Case study : Addis Ababa (International Journal of Engineering and Computer Science, 2019)
For a different item, you can purchase it. There are different costs to purchase that you can analysis the benefit and loses, even if on the software it has different approaches to analysis their wages, the developer company can get their analysis by the different methods.  There are a lot of software cost estimation methods are appearing in different years but still, those methods have their own drawback on making a correct effort and scheduling estimation, here in the paper Today there are different software cost estimation methods that the software company uses from the requirement to implementation phase. Corrected cost estimation supports us to complete the project on planned times and budgets. This paper is mainly presenting the current situations of cost estimation on software placed in Addis Abebas different software compony